185. Characterization of TrueBeam STx for SRS/SBRT treatments with the new phantom StereoPHAN. (December 2018) - Miranti, A.; Bresciani, S.; Leone, R.; Maggio, A.; Di Dia, A.; Bracco, C.; Stasi, M.
Abstract: Purpose: To apply StereoPHAN (Sun Nuclear), a phantom designed for end-to-end commissioning and QA on all parts of the SRS process, in detecting SRS/SBRT paths weaker parts. Methods: Irradiations were performed with TrueBeam STx (Varian) equipped with HD MLC (0.25 cm), while measurements with an Exradin A26 ionization chamber (IC, 0.015 cc, Standard Imaging) inserted in the phantom. Percentage dose difference (%DD) was calculated to evaluate: response linearity with dose, repeatability, dependence on the gantry rotation direction. Moreover, treatment plans with different plan parameters such as number and coplanarity of arcs, energy, dose rate, field dimensions and calculation grid sizes where simulated and measured. Finally, the same measurements where acquired also with the diode array ArcCheck (SunNuclear), the percentage gamma pass (%GP) calculated and isocenter doses reconstructed with 3DVH (Sun Nuclear). Results: Average %DD ± Standard Deviation was (2.6 ± 1)% for the linearity with dose and (3.0 ± 3.2)% for the simulated treatment plans; %DD correlations were found with the dose rate 1600 and 600 MU/min (%DD equal to (4.5 ± 1)% and (2.1 ± 0.8)% respectively, ANOVA p = 0.04) and number of monitor units (linear correlation, Pearson p = 0.01)). No correlation was found between %GP and %DD, while there was not a statistically significant difference between actual StereoPHAN measurements and 3DVH isocenter doses (paired sample t-test, p = 0.13). Conclusions: In this work the new phantom StereoPHAN was applied to evaluate whether %DDs found in SRS and SBRT paths were due to limits of the instruments used to acquire measurements, TPS calculation or linac delivery. Correlation with planning parameters must be furtherly investigated. The lack of correlation between %DD and %GP reflects the intrinsic difference between point dose and dose maps measurements, but the lack of statistical difference between actual and simulated measurements validates StereoPHAN as in comparison with our gold standard measurements performed with ArcCheck.